Financial System of Nurul Falah Masjeed in the Society 5.0 Era Using The Website - Hadi Abdul Aziz; Cahyo Prihantoro (Jurnal Komputer, Informasi dan Teknologi, 2022)
Financial information cannot be viewed at any time because it is still manual. Financial records are not recorded properly which resulted in a lot of missing data and the data search is slow because it is not computerized properly. The development of this system used was the waterfall method which the process consisted of needs analysis, system design, system implementation and testing and management (Saxena & Upadhyay, 2016). Assisting the finance department to record finances in accordance with the rights of the user. The Reporting Process Financial statements become more speedy and accurate. The recommended suggestion for further research is to add a more complete application, including bank reconciliation, capital changes and integrated with related sections to furtherfacilitate the needs required data.